PENYULUHAN KESEHATAN PENGENALAN DAN PENCEGAHAN STUNTING PADA ANAK - Sri Endang Kornita; M. Taufiq; Aidri Iswandi; Azzahra Dinda Gefrisa; Fatimah Zahra Karim; Safna Rahmah Indrayni; Kartika Meynar; Sardiy Sardiy; Kurnia Ningsih; Bella Karmelia; Reski Ramanda (JURNAL PENGABDIAN MANDIRI, 2023)
The problem of stunting is a very important issue and must be addressed together. The main factors that need to be faced in efforts to prevent stunting are poverty and lack of knowledge. Prevention of stunting needs to start when the fetus is in the mother's womb. The importance of a child's First 1000 Days of Life period should not be ignored. To reduce the number of stunting cases, cooperation between the government, health services, social services and the community is very necessary. One of effective way to reduce stunting rates is to increase public awareness through outreach regarding stunting prevention and promotion of healthy eating patterns. In order to make this happen, a community service program has been carried out by the Kukerta team in Ratu Sima Village, South Dumai District, Dumai City, Riau Province. This region has a population of around 10,455 people, with the majority of residents working as entrepreneurs. Based on data from previous reports of Posyandu Tengku Maharatu health workers, there were 3 children who experienced the impact of stunting in the area. Therefore, this program aims to take concrete steps to prevent and reduce stunting rates in Ratu Sima Village. Program activities were carried out at Posyandu Tengku Maharatu on August 12, 2023 using various educational methods, such as outreach, videos, browsers and banners related to stunting prevention and healthy eating patterns. During the implementation of the program, intensive education was carried out regarding preventing stunting and providing healthy food to children in the sub-district. Apart from that, educational materials are also distributed through print media in the form of brochures and banners which are given to the community and local posyandu. Then take part in sweeping and health outreach activities at SDN 002 Ratu Sima by providing education about the importance of eating fish. Overall, this educational program regarding stunting received a positive response from the community, which gives hope that stunting rates can be minimized in the future